Precise Control of Thermal and Redox Properties of Organic Hole‐Transport Materials. (26th October 2018) - Chiykowski, Valerie A.; Cao, Yang; Tan, Hairen; Tabor, Daniel P.; Sargent, Edward H.; Aspuru‐Guzik, Alán; Berlinguette, Curtis P.
Abstract: We report design principles of the thermal and redox properties of synthetically accessible spiro‐based hole transport materials (HTMs) and show the relevance of these findings to high‐performance perovskite solar cells (PSCs). The chemical modification of an asymmetric spiro[fluorene‐9, 9′‐xanthene] core is amenable to selective placement of redox active triphenylamine (TPA) units. We therefore leveraged computational techniques to investigate five HTMs bearing TPA groups judiciously positioned about this asymmetric spiro core. It was determined that TPA groups positioned about the conjugated fluorene moiety increase the free energy change for hole‐extraction from the perovskite layer, while TPAs about the xanthene unit govern the T g values. The synergistic effects of these characteristics resulted in an HTM characterized by both a low reduction potential (≈0.7 V vs. NHE) and a high T g value (>125 °C) to yield a device power conversion efficiency (PCE) of 20.8 % in a PSC.